The Augmented Gravity Model Approach with Multi-Dimensional Panel Data: An Analysis of APEC Countries - Türküz, Elanur; Çağlar, Hatice Nazan (My University, 2018)
The Asia - Pacific Economic Cooperation (APEC) represents a potentially large-scale trade area and has achieved a high level of financial development since its formation in 1989. When APEC was first established its main objectives where to enhance the positive gains, both for the region and the world economy by encouraging the flow of goods, services, capital and technology and reducing barriers to trade among participants. There has been a vast literature using gravity type models to analyze economic phenomena related to international trade nonetheless there has been limited empirical work conducted on APEC. The traditional gravity model of international trade is a relatively new model that explains the bilateral trade flows based on the economic size and geographical distance between countries. This paper investigates a more enhanced panel data approach by using an augmented panel gravity model of the APEC countries by allowing for both indiviual and time effects to be apparent in order to capture time invariant country specific effects with a multidimensional panel data model.
Keywords: International Trade; Gravity Model; Panel Data; Uluslararası Ticaret; Yerçekimi Modeli; Panel Verisi